(3TQM cJGH HWdjehS aj CMcGe GdfLhes - (3CHh GdMSf Ydj Hf QVhGf Hf Ydj Hf LYaQ GdeJWHH GdefLes; (3HWdjehS GdMcje GdbdhPjs
(3ChdgG (B:s
(3bGd CHh GdMSf Ydi Hf QVhGf bUOfG Cf TQM CbGhjd GdMcje HWdjehS ai UfGYI GdbVGA HGdfLhe Ydi GdMhGOK ajbhd Cf GdbVGA HGdfLhe Ydi GdMhGOK UfGYI JfHF Yf eHGOF UGObI s
(3BNQgG (B:s
(3YWGQO HGdMhJ cQHW agPg ESekG bO TQMgG dc aGfYe GdfXQ ajgG hJCedgG hGdHOjgg efg jTGA Edi UQGW eSJbje Je s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(3066) s
Keywords: (3Gdadcs